A necroptosis-related lncRNA signature was identified to predict the prognosis and immune microenvironment of IDH-wild-type GBM - Song, Chong; Zhu, Liwen; Gu, Junwei; Wang, Tong; Shi, Linyong; Li, Chiyang; Chen, Lei; Xie, Sidi; Lu, Yuntao (Frontiers in Oncology, 2022)
Abstract Necroptosis-related genes are essential for the advancement of IDH1-wild-type GBM. However, the putative effects of necroptosis-related lncRNAs (nrlncRNAs) in IDH1-wild-type GBM remain unknown. Using the TCGA and GTEx databases, a nrlncRNA prognostic signature was created using LASSO Cox regression. The median risk score was used to categorize the patients into low and high risk groups. To confirm the validity, univariate, multivariate Cox regression and ROC curves were used. There was enrichment analysis, immune correlation analysis, and drug sensitivity analysis. The expression and phenotype of RP11-131L12.4 in the specimens were verified by in situ experiments. Six nrlncRNAs were used to create a new signature. For 1-, 2-, and 3-year OS, the AUCs were 0.860, 0.793, and 0.788, respectively. Patients in the low-risk group had a better prognosis, stronger immune function activity, and more immune cell infiltration. However, enrichment analysis revealed that the malignant phenotype was more prevalent in the high-risk group. RP11-131L12.4 was found in significant concentrations in tumors and was found to be negatively associated with patient prognosis. The signature of nrlncRNAs may aid in the formulation of tailored and precise treatment for individuals with IDH1-wild-type GBM.